Dissociation of the dimeric SecA ATPase during protein translocation across the bacterial membrane - Or, Eran (Oxford University Press, 2002)
The ATPase SecA mediates post-translational translocation of precursor proteins through the SecYEG channel of the bacterial inner membrane. We show that SecA, up to now considered to be a stable dimer, is actually in equilibrium with a small fraction of monomers. In the presence of membranes containing acidic phospholipids or in certain detergents, SecA completely dissociates into monomers. A synthetic signal peptide also affects dissociation into monomers. In addition, conversion into the monomeric state can be achieved by mutating a small number of residues in a dimeric and fully functional SecA fragment. This monomeric SecA fragment still maintains strong binding to SecYEG in the membrane as well as significant in vitro translocation activity. Together, the data suggest that the SecA dimer dissociates during protein translocation. Since SecA contains all characteristic motifs of a certain class of monomeric helicases, and since mutations in residues shared with the helicases abolish its translocation activity, SecA may function in a similar manner.